Feline pulmonary carcinoma: Gross, histological, metastatic, and immunohistochemical aspects. Issue 1 (January 2023) - Santos, Igor R.; Raiter, Jacqueline; Lamego, Éryca C.; Bandinelli, Marcele B.; Dal Pont, Tainah P.; Siqueira, Kalvin F.; Almeida, Bruno A.; Panzeira, Welden; Sonne, Luciana; Driemeier, David; Pavarini, Saulo P.
Feline pulmonary carcinoma (FPC) is an uncommon neoplasm with unique morphological features. We describe the gross, histological, metastatic, and immunohistochemical aspects of FPC, based on postmortem examinations from an 11-year retrospective study. Thirty-nine cases were selected. Predispositions were observed in senior ( P < .001) and Persian ( P = .039) cats. There were three gross patterns of the pulmonary tumors: (a) a large nodule and additional smaller nodules, (b) a solitary nodule, and (c) small, multifocal to coalescent nodules. Extrapulmonary metastases were present in 22/39 cases (56.4%), mainly in the regional lymph nodes (17/39, 43.5%), skeletal muscles (9/39, 23%), kidneys (6/39, 15.3%), and parietal pleura (4/39, 10.2%). The primary tumor size was correlated with the occurrence of extrapulmonary metastases ( P = .002). Histologically, the tumors were classified as papillary adenocarcinoma (19/39, 48.7%), adenosquamous carcinoma (ADS) (8/39, 20.5%), acinar adenocarcinoma (6/39, 15.3%), solid adenocarcinoma (3/39, 7.6%), lepidic adenocarcinoma (2/39, 5.1%), and micropapillary adenocarcinoma (1/39, 2.5%). By immunohistochemistry, 39/39 cases (100%) were positive for pancytokeratin, 34/39 (87.1%) for thyroid transcription factor-1, and 8/39 (20.5%) for vimentin. Immunoreactivity for p40 was detected in the squamous component of all ADSs (8/8, 100%) and occasionally in the glandular component of adenocarcinomas (10/31, 32.2%). Napsin A expression was absent in all feline tissue tested. The results indicate that a modified and simplified histological classification based on current human and domestic animal systems is appropriate for cats. Additionally, this study highlights the utility of p40 as an immunohistochemical marker for the diagnosis of FPC with squamous differentiation.